Establishment of health management package for native sheep of Bangladesh - Islam, KBM Saiful; Ershaduzzaman, Md; Munsi, Md Nuruzzaman; Kabir, Md Humayun; Das, Sompa; Kabir, Md Hazzaz Bin (Research in Agriculture Livestock and Fisheries, 2016)
The present study was designed to explore the disease status of sheep in Bangladesh with the aim of developing health management package for sheep for better and efficient sheep production in Bangladesh. Both retrospective and prospective investigations on the incidence and prevalence of different diseases of sheep have been conducted in the study areas. Information on the disease related factors like health status, sex and age, vaccination, deworming, etc. were collected. Samples (faeces, blood, etc.) were collected from the diseased/dead animals and preserved following the standard procedure. Faecal samples were examined to determine the parasitic loads and faecal as well as blood samples were examined to determine any protozoan infection present in the study animals. Samples from diarrhoeic animals were studied to isolate and identify causal organisms. Antibiotic resistance and sensitivity studies of the aetiological agents responsible for common infectious diseases in sheep were also conducted in order to suggest the most suitable antibiotic to treat the concerned diseases in the field. Since helminthic infections, diarrhea, pneumonia and foot rot were found to be the mostly occurring health hazards in sheep of all ages, especial attempts were made to develop herbal based novel approaches to treat and control major intestinal helminthic infestations of sheep. However, gentamicin and ciprofloxacin were found most effective antibiotics and recommended to use in diarrhoeal cases in the field. On the other hand, methanol extract of mahogany seeds (100 mg), betel leaf (100 mg) and dodder (100 mg) were found significantly effective against 100% worms in 2 hours in vitro and thus recommended to be used in the field against helminthic infection in sheep. Therefore, a health management package for native sheep of Bangladesh can be designed using the present findings with some fluctuations for different sites after doing the in vivo evaluation of the medicinal plants used in this experiment. Res. Agric., Livest. Fish.3(1): 151-155, April 2016